2006
DOI: 10.1038/sj.jp.7211439
|View full text |Cite
|
Sign up to set email alerts
|

New insights into spontaneous intestinal perforation using a national data set: (2) two populations of patients with perforations

Abstract: Background: Spontaneous intestinal perforation (SIP) is increasingly common in the premature infant and has been demonstrated to be associated with early postnatal administration of glucocorticoids and indomethacin. Before survival of the extremely low birth weight (ELBW) infant, SIP was thought to be a rare, congenitally acquired disease sporadically affecting the muscularis of the distal intestine. These disparate views of etiology have not been previously reconciled in the literature.Objectives: (1) To esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
59
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 9 publications
7
59
1
Order By: Relevance
“…These and our data of the early administration of ibuprofen within the first 3 days of life and SIP are similar to the observations with indomethacin and SIP suggesting a possible link with drug metabolism (see below). 14,15 Further, our data suggest that the incidence of SIP with ibuprofen is similar to the 2 to 8% incidence reported with indomethacin use previously. 22,24 Although most studies have not reported the timing of perforation in relation to the medical treatment of PDA, Shorter et al 25 noted focal perforation about 7 days following the last dose of indomethacin treatment of PDA.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…These and our data of the early administration of ibuprofen within the first 3 days of life and SIP are similar to the observations with indomethacin and SIP suggesting a possible link with drug metabolism (see below). 14,15 Further, our data suggest that the incidence of SIP with ibuprofen is similar to the 2 to 8% incidence reported with indomethacin use previously. 22,24 Although most studies have not reported the timing of perforation in relation to the medical treatment of PDA, Shorter et al 25 noted focal perforation about 7 days following the last dose of indomethacin treatment of PDA.…”
Section: Discussionsupporting
confidence: 68%
“…18 Although NEC and SIP occur in the same population of infants, SIP occurs earlier between 4 to 14 days of age, with a peak incidence between 6 to 9 days and occurs more often in smaller and more immature infants. 14,17,18 The clinical characteristics of infants treated with ibuprofen and who developed SIP were similar to those described previously. 15,17,19,20 Infants in our study with bowel perforation were also of younger GA, had lower birth weight and developed perforation towards the end of first week of life.…”
Section: Discussionsupporting
confidence: 59%
“…All the 13 cases had either respiratory distress or polycythemia before NEC occurred. Eleven of the thirteen were fed before NEC developed, but it is not clear whether the two who were never fed had what today we would define as NEC, or rather had another condition such as SIP [13][14][15] or congenital infarction of the colon. 15 In that report, Thilo et al 12 suggested that to reduce early cases of NEC, feedings should be given more cautiously to neonates who had respiratory distress or polycythemia.…”
Section: Discussionmentioning
confidence: 99%
“…SIP is an example of a condition sometimes confused with NEC. [13][14][15] Human milk feeding programs are not likely to reduce the prevalence of SIP, since many or most cases of SIP occur before the first feeding. 4 Similarly, viral gastroenteritis might be an entity distinct from classical NEC.…”
Section: Discussionmentioning
confidence: 99%
“…The increase risk of chronic lung disease (CLD) is thought to be secondary to its inhibitory effects on surfactant production and stimulatory effects on proinflammatory mediators in the lung [5]. Postnatal indomethacin use is associated with intestinal perforation and acute renal dysfunction in premature infants [2,14]. More recently antenatal indomethacin has been associated with PVL in premature infants (Amin SB, in press).…”
mentioning
confidence: 99%